2023
DOI: 10.26668/businessreview/2023.v8i4.1107
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Strategic Thinking, Knowledge-Oriented Leadership, and Employee Creativity in Higher Education Institutes

Abstract: Purpose: The aim of this study is to examine strategic thinking and knowledge-oriented leadership influence employees' creativity in the setting of Jordanian private universities.   Theoretical framework: The study employed Path Goal Theory to clarify the interaction of the variables used in Higher Education Institutes to address the issue.   Design/methodology/approach: The research used a “partial least squares-structural equation modeling” approach to examine the gathered data. For analysis purpose, was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…This proposition posits that leaders who emphasize prioritization, inspiration, and the cultivation of knowledge possess the capacity to influence the degree to which business intelligence capabilities affect an organization's agility. Moreover, this discovery elucidates the moderating role of knowledge-oriented leadership by Alzghoul et al (2023a). This finding underscores the significance of leadership's involvement in effectively overseeing knowledge dynamics within various industries, as it directly affects the use of business intelligence capabilities.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This proposition posits that leaders who emphasize prioritization, inspiration, and the cultivation of knowledge possess the capacity to influence the degree to which business intelligence capabilities affect an organization's agility. Moreover, this discovery elucidates the moderating role of knowledge-oriented leadership by Alzghoul et al (2023a). This finding underscores the significance of leadership's involvement in effectively overseeing knowledge dynamics within various industries, as it directly affects the use of business intelligence capabilities.…”
Section: Discussionmentioning
confidence: 56%
“…Alzghoul et al (2023a) andNusrat et al (2022) primarily underscore its effect on creativity, it can be hypothesized that such leadership…”
mentioning
confidence: 99%
“…However, to achieve this goal, knowledge-oriented leadership must be matched with the suitable organizational compatibility. The study Alzghoul et al (2023) investigates how strategic thinking and knowledge-oriented leadership drive the creative performance of employees in the Arab HEI.…”
Section: Knowledge-oriented Leadershipmentioning
confidence: 99%
“…First, prior studies have demonstrated the positive impact of knowledge-oriented leadership on team performance virtually [16] and revealed that leaders can boost team performance [17]. KOLs are central in disseminating knowledge directly affecting team performance [18]. From one perspective, leaders can create an environment where participants can advance and expand their transformational skills to improve their knowledge and acquire quick but relevant knowledge [19].…”
Section: Of 20mentioning
confidence: 99%